(untitled) (Tanzania Medical Journal, 2009)
This article reports a case of fibro-osseous lesion, which was clinically and radiologically, diagnosed as ossifying fibroma but histologically proved to be fibrous dysplasia. A 17- year- old boy presented with an 8- months history of a swelling on the left angle of the mandible which was firm with a normal overlying skin. Radiographic evaluation of the swelling showed a well defined radiopaque mass with extension to the ramus. Based on the history, clinical and radiographic features a diagnosis of ossifying fibroma was reached. However, intra- operatively no calcified mass was found within the swelling but rather diffuse heamorrhages of the spongiosa were found. Incisional biopsy was taken from which results showed a non-capsulated lesion containing multiple trabeculae of metaplastic bone dispersed in a reactive moderately cellular vascularised fibrous stroma that was consistent with the diagnosis of fibrous dysplasia. The radiographic and histological confusion surrounding the diagnosis of these lesions are discussed.The importance of a combined approach to diagnosis is emphasized.. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 35-36